How disordered is my protein and what is its disorder for? A guide through the "dark side" of the protein universe. Issue 1 (1st January 2016) - Lieutaud, Philippe; Ferron, François; Uversky, Alexey V.; Kurgan, Lukasz; Uversky, Vladimir N.; Longhi, Sonia
ABSTRACT: In the last 2 decades it has become increasingly evident that a large number of proteins are either fully or partially disordered. Intrinsically disordered proteins lack a stable 3D structure, are ubiquitous and fulfill essential biological functions. Their conformational heterogeneity is encoded in their amino acid sequences, thereby allowing intrinsically disordered proteins or regions to be recognized based on properties of these sequences. The identification of disordered regions facilitates the functional annotation of proteins and is instrumental for delineating boundaries of protein domains amenable to structural determination with X-ray crystallization. This article discusses a comprehensive selection of databases and methods currently employed to disseminate experimental and putative annotations of disorder, predict disorder and identify regions involved in induced folding. It also provides a set of detailed instructions that should be followed to perform computational analysis of disorder.